Kristendom i grænseland - Kastfelt, Niels (Dansk Teologisk Tidsskrift, 2018)
This article discusses general historiographical perspectives emerging from a religious encounter between Danish missionaries and the Bachama people in northern Nigeria in the twentieth century. The general points relate to the role of Christian missionaries in the making of modern Christianity. It is argued that missionaries should be seen as the spearheads of modern Christianity through their experience of religious pluralism and relativism in religious encounters outside Europe. The paper uses the concept of the border to characterise a particular “borderland Christianity” emerging from missionary situations. By way of conclusion it is argued that the borderland experience of missionaries was made part of Western Christianity and constitutes a potentially important but neglected part of the historical development of Christianity in the modern world.